Costing of a hospital-based outbreak of poultry-borne salmonellosis. - Yule, B. F. (Cambridge University Press, 1988)
Poultry-borne salmonellosis is the most common form of foodborne infection in Scotland for which the vehicle can be identified, yet little is known about the costs imposed on society by this disease, or the costs of preventing it. The present study identifies and values the costs of a hospital based outbreak of poultry-borne salmonellosis. Account is taken of costs falling on individuals, the health services and society as a whole. Depending on assumptions made about the value of 'intangibles', the cost of the outbreak is estimated to be between pounds 200,000 and pounds 900,000.